PENGARUH INOVASI PRULINK NEXTGEN TERHADAP ATTITUDE (STUDI PADA KONSUMEN PT PRUDENTIAL LIFE ASSURANCE CABANG XYZ) - Annette Zaneta Zaluchu; Arianis Chan; Pratami Wulan Tresna (POLITEKNIK LP3I JAKARTA, 2024)
Innovation in the insurance industry fundamentally aims to meet consumer needs and expectations while adhering to existing regulations. This research aims to investigate the influence of PRULink NextGen innovation on consumer attitudes at PT Prudential Life Assurance Branch XYZ. This type of research is quantitative research with a simple linear regression analysis method. The data used are sourced from questionnaires as primary data, and interviews as well as literature studies as secondary data sources. The population of this research is customers or potential customers who have been prospected about PRULink NextGen by marketing staff of PT Prudential Life Assurance Branch XYZ. This research uses purposive sampling technique as a non-probability sampling technique with a sample size of 100 people. Testing and data analysis are conducted using SPSS 25.0. The results of this research indicate a significant influence of PRULink NextGen innovation on consumer attitudes at PT Prudential Life Assurance. Key words: innovation, attitude, PRULink NextGen